Translation and folding of single proteins in real time - Wruck, Florian; Katranidis, Alexandros; Nierhaus, Knud H.; Büldt, Georg; Hegner, Martin (Proceedings of the National Academy of Sciences - PNAS, 2017)
Protein biosynthesis is inherently coupled to cotranslational protein folding. Folding of the nascent chain already occurs during synthesis and is mediated by spatial constraints imposed by the ribosomal exit tunnel as well as self-interactions. The polypeptide’s vectorial emergence from the ribosomal tunnel establishes the possible folding pathways leading to its native tertiary structure. How cotranslational protein folding and the rate of synthesis are linked to a protein’s amino acid sequence is still not well defined. Here, we follow synthesis by individual ribosomes using dual-trap optical tweezers and observe simultaneous folding of the nascent polypeptide chain in real time. We show that observed stalling during translation correlates with slowed peptide bond formation at successive proline sequence positions and electrostatic interactions between positively charged amino acids and the ribosomal tunnel. We also determine possible cotranslational folding sites initiated by hydrophobic collapse for an unstructured and two globular proteins while directly measuring initial cotranslational folding forces. Our study elucidates the intricate relationship among a protein’s amino acid sequence, its cotranslational nascent-chain elongation rate, and folding.